Dimethylsulfoxide-induced differentiation and hemoglobin synthesis in tissue cultures of rat erythroleukemia cells transformed by 7,12-dimethylbenz(a)anthracene. - Kluge, N (1976)
Permanent cell lines from transplantable tumors from 7, 12-dimethylbenz(a)anthracene-induced erythroleukemia of the rat were established. These cell lines maintain their erythroid nature. Erythroid differentiation can be induced by dimethylsulfoxide. This is shown by decrease in cell size, appearance of red and benzidine positive cells, and induced synthesis of four out of six adult globin chains.